The United States - King, David C.; Anderson, Charlotte C. (Boston : Houghton Mifflin, 1976)
A social science textbook discussing the cultural and social life of the United States and contrasting it with that of other countries.
Includes index.
Keywords: United States -- History -- Juvenile literature